2023
DOI: 10.30935/ojcmt/13366
|View full text |Cite
|
Sign up to set email alerts
|

Public perceptions towards ChatGPT​ a​s the​ Robo​-Assistant

Abstract: The widespread adoption of digital technologies in various economic activities paves the way for the establishment of a unified digital space. ChatGPT, an artificial intelligence language model, can generate increasingly realistic text, with no information on the accuracy and integrity of using these models in scientific writing. This study aims to investigate factors influencing public perceptions toward the acceptance of ChatGPT as the Robo-Assistant, using a mixed method. The quantitative approach in this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 42 publications
0
0
0
1
Order By: Relevance
“…The findings were in agreement with a study conducted by , which confirmed that the effects of the Starlink project on the competitive structure of the Internet service provider market in Thailand can be attributed to the utilisation of home internet. Jangjarat et al (2023) showed that ChatGPT awareness and usage were influenced by variables like social media usage. In this study, using TikTok was strongly associated with an increased impact of the Starlink project on legal systems, regulations, and national security in Thailand, with an increase of 8.117.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings were in agreement with a study conducted by , which confirmed that the effects of the Starlink project on the competitive structure of the Internet service provider market in Thailand can be attributed to the utilisation of home internet. Jangjarat et al (2023) showed that ChatGPT awareness and usage were influenced by variables like social media usage. In this study, using TikTok was strongly associated with an increased impact of the Starlink project on legal systems, regulations, and national security in Thailand, with an increase of 8.117.…”
Section: Discussionmentioning
confidence: 99%
“…The dependent variable was the potential Starlink's impact on legal systems, regulations, and national security. According to Jangjarat et al (2023), binary regression is a statistical method used to examine the relationship between one or more explanatory variables and a single binary output variable. Therefore, binary regression was employed to analyse the collected data.…”
Section: Methodsmentioning
confidence: 99%
“…AI chatbots can be designed to assess students' knowledge, identify areas where they need improvement, and suggest appropriate learning resources or strategies. By employing AI chatbots, education systems can enhance student engagement, improve learning outcomes, and streamline communication between learners and educators (Jangjarat et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Kehadiran ChatGPT yang ditanggapi dengan berbagai respon, baik yang mendukung penggunaannya maupun menolaknya, memiliki berbagai implikasi. Selain itu, penggunaan ChatGPT dipengaruhi oleh berbagai variabel seperti gender, pendidikan, dan juga penggunaan media sosial (Jangjarat et al, 2023).…”
Section: Alasan Belum Atau Tidak Menggunakan Chatgpt Untuk Keperluan ...unclassified